Familias, Cambios Normativos y Representaciones Sociales de alumnos/as de Derecho (Families, Regulatory Changes and Social Representations of Law Students) - Agustina Perez; Daniela Maria Jose Zaikoski Biscay (Oñati Socio-Legal Series)
As an exploratory research and through the administration of a questionnaire to law students at University of La Pampa (Argentina), we analyze the perceptions they have about the right to form a family as a social relevant subject. A process of legal reforms related to adapt national regulations to the international law of human rights mandate is taking place in Argentina, therefore investigating about what meaning, extension and content future law operators adjudge to certain rights has turned relevant. It is possible to conclude, based on the answers provided by the alumni, that they have a limited perception of the concept suggested, anchored in the classic and traditional perspective of family law, with a lack of presence of phenomena such as the use of assisted reproductive technics, equal marriage, gender identity and diversity, the right to form a family as a fundamental human right, access to justice, among others.